2017
DOI: 10.1111/aab.12401
|View full text |Cite
|
Sign up to set email alerts
|

Bruchid pest management in pulses: past practices, present status and use of modern breeding tools for development of resistant varieties

Abstract: Bruchids (Callosobruchus spp.) are recognised as the most detrimental storage pest of pulses, especially in the tropics and subtropics. They invade matured pods as well as seeds during storage and, to some extent, farming fields, in turn reducing the net yield of the crops. Several approaches including cultural, biological, physical and chemical control measures have been implemented with the aim of managing these pests, but none of these have been successful across time and space. Recently, transgenic-and mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(20 citation statements)
references
References 109 publications
0
20
0
Order By: Relevance
“…The seed coat can also hamper penetration into the seed because it contains biochemical defense barriers (alkaloids, polyphenols, lectins, proteinase inhibitors, α-amylase inhibitors, etc.) involved in the reduction of fertility and/or oviposition, the increase of development time and/or mortality of larvae or adults (Mishra et al, 2018). The accessions “QUASAR,” “109.669,” and “223303” that showed a low % EH but high % SD, could trigger very early and/or intense antibiosis mechanisms that prevent the larvae that have managed to penetrate the seed coat from developing inside (Macel and Dam, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The seed coat can also hamper penetration into the seed because it contains biochemical defense barriers (alkaloids, polyphenols, lectins, proteinase inhibitors, α-amylase inhibitors, etc.) involved in the reduction of fertility and/or oviposition, the increase of development time and/or mortality of larvae or adults (Mishra et al, 2018). The accessions “QUASAR,” “109.669,” and “223303” that showed a low % EH but high % SD, could trigger very early and/or intense antibiosis mechanisms that prevent the larvae that have managed to penetrate the seed coat from developing inside (Macel and Dam, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Biological control has been attempted by using predators and parasitoids (Titouhi et al, 2017) or by applying plant essential oil treatments (Jemâa, 2014; Amzouar et al, 2016; Titouhi et al, 2017). In addition, agronomical and cultural practices have also been applied (Keneni et al, 2011; Mishra et al, 2018). Nonetheless, their effectiveness is limited and their use in large production areas implies a considerable economic investment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have demonstrated Callosobruchus chinensis attacks on P. vulgaris in silos, stacks, and barns throughout the world causing qualitative and quantitative damage by both larvae and the adults [3]. C. chinensis accounts for 60% loss of weight and 66.3% loss of protein content of P. vulgaris [4].…”
Section: Introductionmentioning
confidence: 99%
“…Studies are being conducted on strategies to reduce common bean damage and losses caused by C. chinensis [4]. Farmers use banned and highly toxic synthetic insecticides in their quest to protect agricultural products, including stored bean seeds.…”
Section: Introductionmentioning
confidence: 99%